Metal contamination and stability of household bleach and specially-formulated sodium hypochlorite for endodontic use - Afiq Azizi Jawami; Soo, Eason; Dalia Abdullah; Kia, Amy Cheen Liew; Mariati Abd Rahman (Penerbit Universiti Kebangsaan Malaysia, 2022)
The aims of this in vitro study were to investigate metal contamination and short-term stability of two types of household bleach and a specially-formulated sodium hypochlorite (NaOCl) for endodontic use. The first part of the study was to compare traces of metal elements (Cu, Fe and Ni) between the two types of household bleach (Clorox and Milton) and a specially-formulated NaOCl (CanalProTM 3% NaOCl, Coltene, Whaledent)) using UV spectrophotometer. The second part of the study was to compare the available chlorine and pH of these different NaOCl formulations at different temperatures. Chemical stability of the NaOCl was assessed by measuring the amount of free available chlorine (FAC) using the iodometric titration assay at the temperature of 15, 30, 45, and 60 °C. The pH of the solutions was measured using calibrated pH meter. The results showed that Milton contained significantly higher concentration of Cu, Fe and Ni compared with the other formulations (P < 0.001). Concentrations of Fe detected in Clorox and CanalPro were higher than in the control, distilled water (P < 0.05). In all NaOCl samples, the concentration of available chlorine increased with temperature. Concomitantly, there was a significant decrease in pH with increasing temperature (P < 0.001) with all the NaOCl formulations. In conclusion, traces of metal remnants could be observed in all the NaOCl formulations, especially in Milton. Heating the NaOCl increases the FAC and decreases its pH.